Detection of subclinical atherosclerosis and diastolic dysfunction in patients with schizophrenia - Ünsal C (Dove Medical Press, 2013)
Cüneyt Ünsal,1 Mustafa Oran,2 Hande Oktay Tureli,3 Seref Alpsoy,4 Sema Yesilyurt,5 Mehtap Arslan,6 Birol Topcu,7 Osman Karakaya,8 Erhan Kurt6 1Department of Psychiatry, Namik Kemal University, School of Medicine, Tekirdag, Turkey; 2Department of Internal Medicine, Namik Kemal University, School of Medicine, Tekirdag, Turkey; 3Department of Cardiology, Bakirkoy Dr Sadi Konuk Education and Research Hospital, Istanbul, Turkey; 4Department of Cardiology, Namik Kemal University, School of Medicine, Tekirdag, Turkey; 5Department of Psychiatry, Bağcilar Training and Research Hospital, Istanbul, Turkey; 6Department of Psychiatry, Bakirkoy Training and Research Hospital for Psychiatry Neurology and Neurosurgery, Istanbul, Turkey; 7Department of Biostatistics, Namik Kemal University, School of Medicine, Tekirdag, Turkey; 8Department of Social Service, Yalova University, Faculty of Economics and Administrative Sciences, Yalova, Turkey Background: Patients with schizophrenia have a higher risk for cardiovascular diseases, which is associated with early mortality compared with the nonschizophrenic population. Early diagnosis of cardiovascular diseases in asymptomatic periods in patients with schizophrenia would enhance their quality of life and reduce mortality. Echocardiography, carotid ultrasonography, and ankle brachial index (ABI) measurement are known to be beneficial methods of detecting subclinical cardiovascular diseases and of risk stratification. The present study investigated carotid intima media thickness (CIMT) and ABI and echocardiographic parameters measured via conventional and tissue Doppler echocardiography in patients with schizophrenia in comparison with a control group. Methods: The present case-control study included 116 patients with schizophrenia and 88 healthy patients. Participants with any current comorbid psychiatric disorder, current or lifetime neurological and medical problems, current coronary artery disease, diabetes, hypertension, hypothyroidism, or hyperthyroidism or who were using antihypertensives, antidiabetic agents, or antiobesity drugs were excluded. High-resolution B-mode ultrasound images were used to measure CIMT. Conventional and tissue Doppler measurements were performed according to the recommendations of the American Society of Echocardiography. Results: Low ABI, mitral ratio of the early (E) to late (A) ventricular filling velocities, septal E´, septal S´, lateral E´, lateral S´, septal E´/septal A´, lateral E´/lateral A´, and high septal A´, mitral E/septal E´, mitral E/lateral E´, and CIMT values were observed in the schizophrenia group compared with the control group. Conclusion: Doppler parameters supported the hypothesis that patients with schizophrenia are at high risk for cardiovascular diseases. Keywords: schizophrenia, carotid intima media thickness, ankle brachial index, tissue Doppler echocardiography